(untitled) (European Journal of Pure and Applied Mathematics, 2023)
The principle objective of this research is to present generalised functions ideas which are: fuzzy generalised continuous, generalized strongly continuous, generalized irresolute, generalized open and closed mapping, and the last part is the homomorphism in fuzzy bitopological spaces. We also study the relationships between them, their characteristics, their composition, and some important theories and counterexamples.